Project success criteria, critical success factors (CSF), and agile projects - Bilir, Canser (IGI Global, 2021)
There have been major developments in project management over the years; however, the success rates of projects are still far from the desired levels. The number of studies focusing on project success has been increasing over the last decades. This chapter reviews the concept of project success, project success criteria, and CSF by narrowing the focus from generic projects to IT and then agile projects. The review revealed that client satisfaction has a critical role in the perceived success of the project, along with iron triangle (cost, budget, scope). It is widely accepted that some CSF are dependent on the context of the project. Top management support, communication, clear and linked project objectives, user involvement, teamwork, and effective planning are critical factors in IT projects. There are two differences in the evaluation of the success between agile and traditional software projects: frequency of the evaluation and a stronger emphasis on ensuring customer satisfaction. There is higher importance on people-related factors and customer involvement in agile projects.
Naidoo, V., & Verma, R. (Eds.). (2022). Contemporary Challenges for Agile Project Management. IGI Global. https://doi.org/10.4018/978-1-7998-7872-8